O sistema de avaliação do rendimento escolar do Estado do Rio Grande do Sul - SAERS: institucionalização - Koetz, Carmen Maria (Universidade do Vale do Rio dos Sinos, 2011)
This is a study about the history of the institutionalization of the Evaluation System of the State of Rio Grande do Sul as a public policy for the educational evaluation. It describes the first editions, from 1996 to 1998, as an Evaluation System of the Public Schools of the State, and after 2005, when it was already the Evaluation System of the Educational Performance of the State of Rio Grande do Sul (SAERS) up to the issues from 2007 to 2009. This study is organized by the government period in which these evaluation processes occurred: the government of Antonio Britto Filho - the first three editions (1996/1997/1998), the government of Germano Rigotto, in which a single evaluation was conducted as a pilot project linked to a Management Contract (2005) and the government of Yeda Crusius Ronrato (2007/2008/2009). The methodology applied is qualitative, comprehending the collection and analysis of normative legal documents, the analysis of the information published in newspapers of the state and the semi-structured interview. The focus of this study is the description of the operation, the goals and the purpose of the educational evaluation system of Rio Grande do Sul, including the development and content of the tests applied in each edition of the evaluation process, the number of schools and students that were evaluated, based on the research and analysis of normative documents emitted by the government, by the State Board of Education and by outsourced companies that were hired as service providers. In this study, the results of each issue of the evaluation process that were published in the newspapers, in the web site of the Department of Education of the State and in a major newspaper of Rio Grande do Sul are discussed. The conclusion is that, in every governmental change, new concepts and practices related to the educational policies of evaluation were applied in Rio Grande do Sul, in order to check the performance of the students. The results show that the Evaluation System can be considered as a diagnostic of the quality of the public education in the state, whose goal is to promote alternatives to improve the educational reality of Rio Grande do Sul.
Keywords: Avaliação externa; Política pública de avaliação educacional; Sistema de Avaliação do Rendimento Escolar do Estado do Rio Grande do Sul - SAERS; External evaluation; Public policies for educational evaluation; Evaluation System of the Educational Performance of the State of Rio Grande do Sul; ACCNPQ::Ciências Humanas::Educação